2008
DOI: 10.2320/matertrans.mbw200734
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Temperature and Strain Rate on Mechanical Behavior of a Cu<SUB>45</SUB>Zr<SUB>45</SUB>Al<SUB>5</SUB>Ag<SUB>5</SUB> Bulk Glassy Alloy

Abstract: Since the invention of bulk glassy alloys, a number of studies have been performed at ambient temperatures or above. However, little is known about mechanical properties of bulk glassy alloys at cryogenic temperatures. In this study, we investigated the effects of temperature and strain rate on the mechanical properties of a Cu 45 Zr 45 Al 5 Ag 5 bulk glassy alloy fabricated by high pressure die casting methods. Compression tests were performed for the Cu 45 Zr 45 Al 5 Ag 5 bulk glassy alloy rods with a diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
2
11
1
Order By: Relevance
“…13 225 at 77 K might also be ascribed to the decrease of the STZ volume due to low temperature, where nano-scaled "chevron" patterns rather than vein patterns on the low temperature fracture surface indicate an apparent decrease in the plasticity [7]. While for other BMGs [49][50][51][52][53][54][55] with both enhancements of yield strength and plasticity under compression when the test temperatures decrease from room temperature to liquid nitrogen temperature (77 K), a lower test temperature might introduce a brittle failure, i.e. ductile-to-brittle transition.…”
Section: Discussionmentioning
confidence: 99%
“…13 225 at 77 K might also be ascribed to the decrease of the STZ volume due to low temperature, where nano-scaled "chevron" patterns rather than vein patterns on the low temperature fracture surface indicate an apparent decrease in the plasticity [7]. While for other BMGs [49][50][51][52][53][54][55] with both enhancements of yield strength and plasticity under compression when the test temperatures decrease from room temperature to liquid nitrogen temperature (77 K), a lower test temperature might introduce a brittle failure, i.e. ductile-to-brittle transition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the strengthened materials at low temperature usually behave more brittle. However, very interestingly, it is reported that BMGs at cryogenic temperature show enhanced plasticity in compression [1][2][3][4][5][6][7][8], even in tension [9,10]. Such plasticity improvement was attributed to multiple-nucleation of shear bands at low temperature [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to crystalline alloys, BMGs usually exhibit higher strength with the decrease of the ambient temperature [1][2][3][4][5][6][7][8][9][10]. Its underlying mechanism has been discussed in terms of shear transformation zones (STZs) [1,3,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Consequently, we performed compression tests at cryogenic temperatures and at various strain rates using Cu 45 Zr 45 Al 5 Ag 5 , Zr 55 Al 10 Ni 5 Cu 30 and Ni 60 Pd 20 P 17 B 3 BGA samples. [17][18][19] It was found that the compressive maximum strength and plastic strain prior to failure are higher at cryogenic temperatures than at ambient temperature. Recently, Huang et al 20) reported similar results in compression tests for a Ti 40 Zr 25 Ni 3 Cu 12 Be 20 BGA.…”
Section: Introductionmentioning
confidence: 99%